Human, Nature, and the Ring: Fire and Struggle in Jack London’s Fiction (British Journal of Multidisciplinary and Advanced Studies, 2026)
This article examines Jack London’s short stories The Game (1905) and To Build a Fire (1908) through the lens of literary naturalism and the concept of dignified defeat. It argues that London redefines heroism not as victory over external forces but as moral endurance in the face of inevitable failure. By juxtaposing human confrontation with nature and with another human opponent, the study demonstrates how London foregrounds inner strength, ethical resolve, and perseverance as central markers of human worth. Drawing on close textual analysis and contextualized within American naturalism, the article situates London’s protagonists as figures who achieve moral triumph despite physical annihilation.